DEVELOPMENT OF EXTRACTIVE SPECTROPHOTOMETRIC METHOD FOR THE DETERMINATION OF IRON (III) WITH SCHIFF BASE 2-[(2-HYDROXYPHENYLIMINO) METHYL]-4-NITROPHENOL - Mandhare, Datta B.; Barhate, Vasant D. (International Journal of Current Pharmaceutical Research, 2016)
Objective: A simple spectrophotometric method has been developed for the determination of Iron (III) by using Schiff base 2-[(2-hydroxyphenylimino) methyl]-4-nitrophenol [HPIMNP]. Methods: HPIMNP extracts Fe (III) quantitatively (99.95%) into chloroform from an aqueous solution of pH range 4.0-6.0. Results: The chloroform extracts show maximum absorption at 510 nm (λ max). Beer's Law is obeyed over the Fe (III) concentration range of 0.5 to 20.0 µg/ml. The Molar absorptivity and Sandell's sensitivity for Fe–HPIMNP system is 5000 L mol ˉ1 cmˉ1 and 0.011 µg cmˉ2respectively. The composition of extracted species is found to be 1: 3 [Fe-HPIMNP] by Job's continuous variation and Mole-ratio method. Interference by various ions has been studied. Conclusion: The proposed method is rapid, sensitive, reproducible and accurate and it has been satisfactory applied for the determination of Iron in Pharmaceutical Samples.